MiR-556-3p mediated repression of klotho under oxidative stress promotes fibrosis of renal tubular epithelial cells - Dong Zhang; Zongying Li; Yuan Gao; Hailing Sun (Scientific Reports)
Abstract Chronic kidney disease (CKD) is a global health issue characterized by renal fibrosis, which leads to irreversible tissue damage. Oxidative stress plays a key role in driving the fibrotic processes associated with CKD. This study investigates the roles of oxidative stress, miR-556-3p, and klotho in renal tubular epithelial cells, focusing on their influence on fibrotic pathways. Using human renal tubular epithelial cells HK-2, we conducted various in vitro assays to measure reactive oxygen species (ROS) levels, cell death, viability, and proliferation. Oxidative stress, induced by H2O2 treatment, was found to suppress klotho expression while increasing the expression of fibrotic markers. Overexpression of klotho mitigated these effects, highlighting its protective role against oxidative stress-induced fibrosis. Moreover, miR-556-3p was upregulated in response to oxidative stress activated transcription factor Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2), contributing to the suppression of klotho. Inhibition of Nrf2, a key regulator of oxidative stress responses, attenuated the expression of miR-556-3p and fibrotic markers. Targeting the Nrf2-miR-556-3p-klotho axis may offer novel therapeutic avenues to restore klotho levels and attenuate renal fibrosis. Our study contributes significantly to the understanding of the molecular mechanisms driving CKD progression and highlights potential targets for future pharmacological intervention.